PENGARUH FINANCIAL DISTRESS, DEBT DEFAULT, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PADA PERUSAHAAN TRANSPORTASI, INFRASTRUKTUR, DAN UTILITAS - Muhammad Rakhmat Aghisna; Ati Sumiati; Unggul Purwohedi (Yayasan Education and Social Center, 2023)
The Influence of Financial Distress, Debt Default, and Company Growth on Receiving Going Concern Audit Opinions in Transportation, Infrastructure, and Utilities Companies Listed on the Indonesia Stock Exchange in 2019-2021. Thesis. Jakarta. Economic Education Study Program Concentration in Accounting Education. Faculty of Economics. State University of Jakarta. 2023. This study aims to determine the effect of financial distress, debt default, and company growth on acceptance of going concern audit opinions in transportation, infrastructure, and utility companies listed on the Indonesia Stock Exchange in 2019 - 2021. The research method used is a quantitative method with secondary data obtained from financial reports available on the Indonesia Stock Exchange with a total sample of 64 companies using purposive sampling technique. The data analysis technique used is descriptive statistical analysis, multicollinearity classic assumption test, whole model test, regression model feasibility test, logistic regression analysis, and hypothesis testing. The results showed that financial distress and debt default had a significant negative effect on acceptance of going-concern audit opinions while company growth had no effect on acceptance of going-concern audit opinions. The coefficient of determination in this study is 31% which indicates the ability of financial distress, debt default, and company growth to explain acceptance of going concern audit opinions while the remaining 69% is explained by other variables